2014
DOI: 10.5152/eurjrheum.2014.004
|View full text |Cite
|
Sign up to set email alerts
|

Serum salusin-α levels in systemic lupus erythematosus and systemic sclerosis

Abstract: Objective: Systemic lupus erythematosus (SLE) and systemic sclerosis (SSc), chronic inflammatory diseases, demonstrate an increased incidence of cardiovascular manifestations and subclinical atherosclerotic disease. Salusin-α is a novel bioactive peptide that suppresses the formation of macrophage foam cells, and its serum level is significantly lower in patients with angiographically proven coronary artery disease. The aims of the study were to assess serum salusin-α level and its potential association with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
1
9
0
2
Order By: Relevance
“…Importantly, we found that overexpression of the salusin- α gene decreased the intima thickness in rabbits. Intimal hyperplasia in atherosclerotic rabbit models is usually caused by excessive accumulation of intracellular lipids by intimal cells [ 27 29 ], and the salusin- α gene has been reported to reduce hypertension and inhibited macrophage foam [ 14 , 15 ]. Thus, the finding that overexpression of salusin- α decreased intimal thickness could be related to inhibition of the proliferation of vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, we found that overexpression of the salusin- α gene decreased the intima thickness in rabbits. Intimal hyperplasia in atherosclerotic rabbit models is usually caused by excessive accumulation of intracellular lipids by intimal cells [ 27 29 ], and the salusin- α gene has been reported to reduce hypertension and inhibited macrophage foam [ 14 , 15 ]. Thus, the finding that overexpression of salusin- α decreased intimal thickness could be related to inhibition of the proliferation of vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this protein is also involved in the prevention of macrophage foam cell formation by downregulating acetyl-coenzyme A acetyltransferase 1 (ACAT1), thereby affecting atherosclerosis [ 10 , 12 , 13 ]. Some reports have shown the negative correlation between salusin- α levels in serum and the degree of vascular stenosis, suggesting that salusin- α may have applications as a diagnostic reference in atherosclerotic disease [ 14 , 15 ]. However, the mechanisms through which salusin- α regulates atherosclerosis in vivo are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The serum IL-6 levels ranged from 4.272±0.4222 to 123.71±81.783 (pg/mL) in SLE patients and 0.93 ± 0.95 to 10.46 ± 4.33 (pg/mL) in healthy controls. A total of 13 studies compared the serum IL-6 levels between SLE patients and healthy controls (23)(24)(25)(27)(28)(29)(32)(33)(34)39,40,43,46). Serum IL-6 levels between active and inactive SLE patients were compared in 9 studies (24)(25)(26)29,31,39,(41)(42)(43).…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…9 Arnett ve ark., yaptıkları çalışmada, birinci derece yakınlarında SSk bulunan bireylerde, SSk gelişme olasılığının arttığını, normal populasyonda SSk gelişme riski %0,026 iken, birinci derece yakınlarında SSk bulunan bireylerde bu riskin %2,6 olduğunu belirtmişlerdir. 37 Nietert ve Silver, çevresel ve mesleksel faktörlerin SSk etiyolojisindeki yerini incelemiş ve bu faktörlerin tek başına SSk etiyopatogenezinde etkili olamayacağını bildirmişlerdir.…”
Section: Discussionunclassified
“…2,8 SSk'nın etiyolojisi tam olarak açıklanamamasına karşın çevresel faktörler, geçirilmiş enfeksiyonlar, mikrokimerizm ve genetik yatkınlık, patojenik sü-reci tetikleyen olası aracılar olarak gösterilmektedir. 9 SSk patogenezinin vaskülopati, immün aktivasyon ve fibroz triadı ile karakterize olduğu kabul edilmektedir. [10][11][12] Mikrovaskülopatinin kapillereskopi ile teşhis edilmesi SSk'nın erken tanısı için önemlidir.…”
unclassified